MODERN VIEWS ON THE MANAGEMENT SYSTEM OF TEACHING STAFF IN VOCATIONAL SCHOOL - Pyshchyk, Olena V. (Educological discourse, 2017)
The article is devoted to the problem of formation of effective system of management of teaching staff in vocational school. Discusses the processes of humanization and democratization of society requires the development of management skill and creativity of the head in the control system of vocational school.